Is Public Education Viable? A Brief Critical Review of Neoliberalism in Education with a Special Focus on the Portuguese Situation - Chagas Lopes, Margarida (Journal of Research in Educational Sciences; Vol 4 No 1 (2013): JRES, Volume IV, Issue 1(6), 2013, 2013)
As well as in other social domains, neoliberalism has been invading education. This trend is leading to a general commodification and to the progressive substitution of some basic values, as the equality of opportunities, by efficiency and competitiveness. At the same time, education policies become more and more shaped by strict economic principles, reflecting the training acquired by decision makers in economics and economics of education courses. That is why we reject, as a critical social scientist, the view that the viability of public education could be discussed uniquely on the grounds of mainstream public economics criteria. On the contrary, that discussion must allow critical pedagogies and alternative approaches to express themselves. Also mainstream clichés must be systematically criticized, as we exemplify in the domain of economics of education. Actually, those are the indispensable complimentary pathways throughout which we can return to education its full meaning as a social service; and also to economics of education its legitimacy as a social science.